1998
DOI: 10.1111/j.1399-6576.1998.tb05100.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline and dextran in normovolaemic and hypovolaemic healthy volunteers increases interstitial and intravascular fluid volumes

Abstract: HSD infusion resulted in increased calculated blood volume with increased HR, MAP, and CVP. These effects were greater in a hypovolaemic situation. The haemodilution was most likely caused by fluid shifts from the intracellular compartment to the interstitial and vascular fluid spaces, eventually increasing diuresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
56
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 16 publications
8
56
1
Order By: Relevance
“…Likewise, it was demonstrated that subcutaneous injections of HS result in robust water drinking by mice (22). In addition, increased diuresis was reported after the administration of hypertonic solutions (28). Therefore, in the HS group, a higher consumption of DSS provided through the drinking water may have occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it was demonstrated that subcutaneous injections of HS result in robust water drinking by mice (22). In addition, increased diuresis was reported after the administration of hypertonic solutions (28). Therefore, in the HS group, a higher consumption of DSS provided through the drinking water may have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been renewed interest in the use of hyperosmolar resuscitation fluids in shock therapy. Infusion of hypertonic saline (HS) results in a rapidly increased intravascular blood volume due to osmotically induced fluid shifts from the extravascular compartments to the vascular bed (28).…”
mentioning
confidence: 99%
“…This leads to a translocation of nearly 4/5 of the administered volume to the interstitium, resulting in edema and tissue hypoxia 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, at least, three times the amount of blood lost should be replaced with crystaloids³. Of the remainder left in the intravascular, about half is eliminated as urine and the other half will form interstitial edema 4 . As a result, there is a great amount of fluid draining into the extravascular space with formation of interstitial edema.…”
Section: Introductionmentioning
confidence: 99%
“…The crystalloids have little effect on volemic expansion because only 20% of the total quantity that is infused remains in the intravascular space 20 minutes after infusion. Half of the infused volume is eliminated as urine, and 30% causes edema [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%